PENGARUH HIGH PERFORMANCE HUMAN RESOURCE MANAGEMENT PRACTICES DAN SELF MANAGEMENT PRACTICES PADA KEPUASAN KERJA KARYAWAN (Studi pada Karyawan Hotel Sahid Raya Yogyakarta) - DIDIEK WIJAYA A., DIDIEK WIJAYA A. (Fakultas Ekonomi UM Metro, 1978)
Abstract This study aimed to determine the effect of High Performance Human Resource Management Practices, which consist of Empowerment, Job Rotation, Employee Participation, and Self Management Practices, which consist of Planning and Goal Setting, Access Management, Catch up Activities and Emotion Management in Employee Job Satisfaction. This research was conducted at Sahid Raya Hotel Yogyakarta. The respondent were permanent employees whom consist of 110 employee. Multiple linier regression analysis, which carried out with the help of the statistics program SPSS Windows Release 13.00, was used to analyze the data, the analysis result showed that job rotation, employee participation, planning and goal setting, access management, and emotion management positively and significantly influenced on employee job satisfaction. While empowerment and catch up activities had no significant effect on employee job satisfaction. However, there was indirectly or small effect. Those empirical findings indicated that employee job satisfaction is important for the company, so Sahid Raya Hotel Yogyakarta needs to pay attention to the factors that can increase employee job satisfaction. Theoretical implications and suggestions for future research are also outlined at the end of the research. Empowerment: Job Rotation, Employee Participation, Planning and Goal Setting, Access Management, Catch Up Activities, Emotion Management, and Job Satis faction.